Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.059
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Investment Motivation and Financial Literacy on Interest in Investing During the COVID-19 Pandemic

Abstract: The purpose of this study is to analyze the influence of investment motivation and financial literacy on investment interest in the capital market. The population used in this study were investor and potential investors at the Investor Gathering event, then sample was selected using purposive sampling technique. Multiple linear regression method was applied. The findings stated that investment motivation and financial literacy either partially or simultaneously have a significant positive effect on investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
2
6
0
1
Order By: Relevance
“…www.ejournal.aibpm.org/index.php/JICPAccording to the results, it was found that investment motivation has an influence on investment interest. The results of this study are supported by the research of Suprihati & Pradanawati (2020) andParanita & Agustinus (2020) which found that investment motivation has an effect on investment interest.…”
supporting
confidence: 84%
“…www.ejournal.aibpm.org/index.php/JICPAccording to the results, it was found that investment motivation has an influence on investment interest. The results of this study are supported by the research of Suprihati & Pradanawati (2020) andParanita & Agustinus (2020) which found that investment motivation has an effect on investment interest.…”
supporting
confidence: 84%
“…The higher the Financial Literacy, the moreInterest in Investing will increase.This finding implies that to generate investmentinterest in the capital market, it is absolutely necessary toincrease the investment motivation of investors. Other than that,during the COVID-19 pandemic, Financial ServicesAuthorities as regulators further improve FinanceLiteracy by disseminating investment in the capital market through virtual media (Paranita & Agustinus, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini berbeda dengan penelitian Chu et al (2016) yang menunjukkan bahwa semakin kurang berani seseorang untuk berinvestasi maka semakin tinggi tingkat financial literacynya, hal ini dikarenakan seseorang berhati-hati dalam berinvestasi untuk mendapatkan return yang baik. Penelitian Romdioni, (2021), Adil et al, (2021), Dewi & Pertiwi, (2021) dan (A. , (Paranita & Agustinus, 2021) menunjukkan bahwa financial literacy mempengaruhi pengambilan keputusan investasi pria ataupun wanita, namun penelitian (Santoso, 2021) membuktikan bahwa financial literacy tidak berpengaruh dalam pengambilan keputusan investasi. Biasanya wanita memiliki financial literacy yang tinggi dibandingkan pria, hal ini dikarenakan wanita yang bersifat risk averse (Septiani, 2013).…”
Section: Pendahuluanunclassified